Community violence exposure and substance use: cross-cultural and gender perspectives - Löfving-Gupta, Sandra; Willebrand, Mimmie; Koposov, Roman; Blatný, Marek; Hrdlička, Michal; Schwab-Stone, Mary; Ruchkin, Vladislav (European child & adolescent psychiatry, 2018)
The negative effects of community violence exposure on child and adolescent mental health are well documented and exposure to community violence has been linked both to a number of internalizing and externalizing symptoms. Our aim was, therefore, to investigate cross-cultural and gender differences in the relationship between community violence exposure and substance abuse. A self-report survey was conducted among 10,575, 12-18 year old adolescents in three different countries, Czech Republic (N = 4537), Russia (N = 2377) and US (N = 3661). We found that in all three countries both substance use and problem behavior associated with it increased similarly along with severity of violence exposure and this association was not gender-specific. It was concluded that in spite of the differences in the levels of violence exposure and substance use cross-culturally and by gender, the pattern of their association is neither culturally nor gender bound.
Keywords: Russia; Adolescents; srovnání kultur; Cross-Cultural Comparison; mladiství; Rusko; mužské pohlaví; Community violence exposure; genderová identita; Exposure to Violence; dítě; Child; Violence; Substance-Related Disorders; ženské pohlaví; poruchy spojené s užíváním psychoaktivních látek; Humans; násilí; vystavení násilí; Gender; Female; Substance use; Adolescent; lidé; Male; Gender Identity